2020
DOI: 10.1080/08989621.2020.1782203
|View full text |Cite
|
Sign up to set email alerts
|

An alarming retraction rate for scientific publications on Coronavirus Disease 2019 (COVID-19)

Abstract: The ongoing Coronavirus Disease 2019 global pandemic has triggered a flurry of associated research publications, numbering to ~137 papers a day since February 2020. This rate of publication appears to be exceptionally high, when compared to research papers published on other similar topics. Searches of COVID-19associated publications on PubMed and Retraction Watch Database indicate that the retraction record appearance rate for COVID-19-related research is also exceptionally high compared to other related res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
104
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(127 citation statements)
references
References 14 publications
5
104
0
3
Order By: Relevance
“…Although the paper on Covid-19 management using antimalarial drugs published in the Lancet had been retracted shortly after its publication, 6 surprisingly, this paper was cited about 68 times, most of the citations occurred before it was retracted, which may have an adverse effect on the therapeutic interventions and approaches based on the weak data and inaccurate results reported in the retracted article, with a negative effect on the health systems and patients. 1 The article processing journey in most journals starts shortly after the submission; as it is first checked by a Publishing Assistant to check the initial appropriateness of this article to the journal, then it is passed to the Editor, who decide if this article is within the journal scope and will add to the specific field knowledge, if passed this stage, it will be sent to be "peer-reviewed" with different levels of review process blindness. 14,15 How much time the article will spend in the review process depends on the reviewer's expertise, organization, and the available time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the paper on Covid-19 management using antimalarial drugs published in the Lancet had been retracted shortly after its publication, 6 surprisingly, this paper was cited about 68 times, most of the citations occurred before it was retracted, which may have an adverse effect on the therapeutic interventions and approaches based on the weak data and inaccurate results reported in the retracted article, with a negative effect on the health systems and patients. 1 The article processing journey in most journals starts shortly after the submission; as it is first checked by a Publishing Assistant to check the initial appropriateness of this article to the journal, then it is passed to the Editor, who decide if this article is within the journal scope and will add to the specific field knowledge, if passed this stage, it will be sent to be "peer-reviewed" with different levels of review process blindness. 14,15 How much time the article will spend in the review process depends on the reviewer's expertise, organization, and the available time.…”
Section: Discussionmentioning
confidence: 99%
“…2 In another study by Yeo-Teh and Tang carried in June 2020, they found that the average rate was 137 papers per day. 1 The most concerning issue of the rush and racing in scientific publications on the newly experienced pandemic resides in the potential for "misinformation" or "disinformation," which may be caused by expressing false or misleading claims combined with a deficiency in the reviewing process, which is considered as the information checkpoint before it gets published to the public. 3,5 This concern was confirmed in a study by Yeo-Teh and Tang where they found that the retraction rate of Covid-19 related articles (since the start of the disease) exceeds the rates of cancer and immunology related articles retraction rates, a prominent example was the article written on the role of antimalarial drugs in the management of Covid-19 patients which was published in The Lancet on May 22nd and retracted on June 4th.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Journals should probably also consider the various Open Review processes [15] and let referees themselves decide whether or not they want to sign their reviews. 4. When publications report quantitative findings, a systematic review of statistical methodology should be included.…”
Section: Open Reviewmentioning
confidence: 99%
“…Many of these publications have contributed to the development of a body of knowledge that has since informed practice but a considerable number of these studies suffer methodological weaknesses, limiting the interpretability of their findings [2] or leading to false claims with a potentially dramatic impact on public health. While some of these studies have already been retracted [3,4], others are still available to the research community and to the public. In addition to the direct threat these publications pose to patient management and public health policies, these low-quality studies also exacerbate the waste of scientific resources [2] that is well-known to plague the scientific system [5].…”
Section: Introductionmentioning
confidence: 99%